The semiotics of performance - De Marinis, Marco (Advances in semiotics., 1993)
"In this brilliant book Marco De Marinis develops a systematic definition of performance in terms of text, a new theoretical object, which he sees as the result of treating theatrical performance as a material object, a mixture of old and new, of the "already said" and the "not yet said." This permits him to view performance as an original combination within a textual structure of pre-existing codes and specific codes that are created anew with each performance and thus recognizable only by abduction."--Jacket